Blacksmith's house, wooden knives: why do legacy firms succeed in promoting digital outcomes but struggle with the digital transformation of their existing business models? - Matheus Franco; Ruy Quadros; Thomas Clauß; Vinicius Minatogawa (Review of Managerial Science, 2025)
Although research recognizes that legacy firms struggle with digital transformation, frequently abandoning initiatives, the underlying mechanisms remain a black box. To tackle this issue, we adopt an Attention-based view lens and follow a multiple case study design with five Brazilian legacy firms as a methodological approach. We draw evidence from longitudinal data spanning six years (2016–2021), triangulating archival data from the companies' annual reports with their websites and formal and informal interviews. Our findings reveal the interplay between attention shortsightedness, resulting in temporal myopia, and the mechanisms that we call the `spinning the slots' for DT and `trendy decision-making' to explain the procedural inconsistency. Therefore, we contribute to DT literature in several ways. First, we expand the DT literature by uncovering strategy-making mechanisms underlying legacy firms' struggle with DT. Second, we challenge the overall positive vision of DT as an enabler of more rational strategic decision-making. We discuss that ambiguity and attention conflicts can lead to silos of garbage can decision-making, where DT can be a result of chance rather than increased rational decisions.
Keywords: L20; M15; 650; Digital transformation; Attention-based view; Temporal myopia; Garbage can; Strategic decision making; Legacy firms